2019
DOI: 10.1016/j.contraception.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of postabortion contraception use in Cambodia

Abstract: To evaluate which characteristics collected at the point of abortion are associated with contraceptive use over the extended post-abortion period for women in Cambodia. Methods The study includes a cohort of 500 women who attended a Marie Stopes International Cambodia clinic for an induced abortion. The primary outcomes are use of effective contraception ≥80% of the time over the four and 12-month period post-abortion. We conducted a bivariate analysis to assess the association between each characteristic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Ross and Winfrey's (2001) secondary analysis of DHS data in 27 countries found that for each increase of one percentage point in stated ITU contraceptives, there was nearly a 1% rise in the actual use of contraceptives. ITU also has been found to have a positive relation to contraceptive continuation; Raine et al (2011) and Adelman, Free, and Smith (2019) found that a higher intent to use a method was associated with a lower risk of discontinuation. However, five papers found null or negative associations between ITU and use (Lutalo et al 2018;Hale et al 2016;Akelo et al 2013;Potard et al 2012;French, Albanese, and Gossett 2016).…”
Section: Reported Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ross and Winfrey's (2001) secondary analysis of DHS data in 27 countries found that for each increase of one percentage point in stated ITU contraceptives, there was nearly a 1% rise in the actual use of contraceptives. ITU also has been found to have a positive relation to contraceptive continuation; Raine et al (2011) and Adelman, Free, and Smith (2019) found that a higher intent to use a method was associated with a lower risk of discontinuation. However, five papers found null or negative associations between ITU and use (Lutalo et al 2018;Hale et al 2016;Akelo et al 2013;Potard et al 2012;French, Albanese, and Gossett 2016).…”
Section: Reported Resultsmentioning
confidence: 99%
“… 2018 ; Tang 2016 ; Johnson et al. 2019 ; Adelman, Free, and Smith 2019 ; Raine et al. 2011 ; Lutalo et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the determinants of contraceptive use after abortion reveal varying results due to contextual differences, study designs and outcomes of interests [ 5 , 23 26 ]. Research also shows that contraceptive uptake is highest when immediately offered on-site, or within less than six months or up to a year [ 23 , 26 29 ]. For instance, Adelman, Free and Smith [ 29 ] examined the predictors of post-abortion contraception at four and 12 months among Cambodian women.…”
Section: Introductionmentioning
confidence: 99%
“…Research also shows that contraceptive uptake is highest when immediately offered on-site, or within less than six months or up to a year [ 23 , 26 29 ]. For instance, Adelman, Free and Smith [ 29 ] examined the predictors of post-abortion contraception at four and 12 months among Cambodian women. They found that previous contraceptive use, intention to use contraception, and number of living children were strongly associated with post-abortion contraception use.…”
Section: Introductionmentioning
confidence: 99%